Transformasi Keuangan UMKM melalui Digitalisasi : Pelatihan dan Pendampingan Aplikasi Pencatatan Keuangan pada Komunitas Preman Super - Nasyiah, Eny Zuhrotin; Nandiroh, Umi (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance digital financial literacy through the use of financial recording applications for the Preman Super MSME community in Malang City. The method consisted of five stages: needs assessment, basic financial management training, digital application training, intensive mentoring, and evaluation and reflection. Data collection was carried out through interviews, observations, and the distribution of questionnaires. The evaluation of the activity was conducted by analyzing the results of the questionnaires, comparing data before and after the activity. The instrument distributed focused on digital financial literacy knowledge. The results of this service activity showed a significant improvement in participants' understanding and skills in recording transactions, separating personal and business finances, and preparing simple cash flow reports using applications such as BukuKas and Lummo. Pre–post test evaluations and practical observations indicated that more than 80% of participants experienced an increase in financial literacy and began consistently applying digital financial recording. This activity had a tangible impact on the partner community and holds the potential to be replicated for other MSME communities facing similar challenges.